Respuesta :

  2x + 4y = 6
- 2x        - 2x
          4y = -2x + 6
           4          4
            y = ⁻¹/₂x + 1¹/₂

A. 4x + 6y = 8
  - 4x        - 4x
            6y = -4x + 8
             6           6
              y = ⁻²/₃x + 1¹/₃
The answer isn't A.

B. 3x + 6y = -7
  - 3x          - 3x
             6y = -3x - 7
              6          6
              y = ⁻¹/₂x - 1¹/₆
The answer is B.

C. 4x + 2y = -6
  - 4x          - 4x
             2y = -4x - 6
              2         2
               y = -2x - 3
The answer isn't C.

D. 6x + 3y = 5
  - 6x         - 6x 
            3y = -6x + 5
             3           3
             y = -2x + 1²/₃
The answer isn't D.

The final answer of this problem is B.